Treatment Planning Session - Lim, Sun; Ru, Jae Il; Jacob, Austin; Kim, Michelle (Caucasus Journal of Health Sciences and Public Health, 2020)
The current presentation will discuss treatment planning based on a clinical case. This case brings together dental students of all four years, thus creating a spiral method of teaching. While the patient is managed and treated by a senior student, junior students present an Evidence-Based (EBD) topic, component of anatomy and general health/medical conditions relevant to the clinical case. The patient JB presented at Tufts University School of Dental Medicine in December of 2018.Patient’s chief complaint was:“to get her teeth back for chewing and eating”. Patient had partial edentulism, generalizedsevere wear and failing restorations. Due to prolonged loss of posterior support patient has lost Vertical Dimension of Occlusion (VDO). The treatment aimed to re-establish correct VDO and occlusal schemestaking into consideration patients’ general health and financial status.